Deciphering the mechanisms, biochemistry, physiology, and social habits in the process of aging - Folake Olubukola Asejeje; Olalekan Bukunmi Ogunro (Archives of Gerontology and Geriatrics Plus)
Aging is a complex journey shaped by interactions among mechanisms, biochemistry, physiology, and social habits. This review explores aging's core facets by uncovering the mechanisms driving cellular senescence, oxidative stress, telomere shortening, and mitochondrial dysfunction.The review also delves into the biochemistry and physiology of aging, shedding light on hormonal shifts, genetic influences, and immune system modifications that contribute to the aging process. It navigates the terrain of social habits linked to aging, considering the profound impact of dietary choices, physical activity, social engagement, and stress management.These elements intricately intertwine, emphasizing the holistic nature of aging. The complex interplay between mechanisms, biochemistry, physiology, and social habits underscores the need for a comprehensive understanding of aging that transcends single disciplines.Deciphering these factors underscores the significance of personalized approaches to healthy aging. Tailoring interventions to individual genetics, lifestyles, and health needs emerges as a critical strategy for optimizing well-being in later life.In conclusion, this review illuminates the multifaceted nature of aging, urging the embrace of complexity and interdependence. By fostering a holistic, personalized approach, individuals can navigate the aging journey with grace, vitality, and resilience.